A survey of 178 NF-Y binding CCAAT boxes. - Mantovani, R (1998)
The CCAAT box is one of the most common elements in eukaryotic promoters, found in the forward or reverse orientation. Among the various DNA binding proteins that interact with this sequence, only NF-Y (CBF, HAP2/3/4/5) has been shown to absolutely require all 5 nt. Analysis of a database with 178 bona fide NF-Y binding sites in 96 unrelated promoters confirms this need and points to specific additional flanking nucleotides (C, Pu, Pu on the 5'-side and C/G, A/G, G,A/C, G on the 3'-side) required for efficient binding. The frequency of CCAAT boxes appears to be relatively higher in TATA-less promoters, particularly in the reverse ATTGG orientation. In TATA-containing promoters the CCAAT box is preferentially located in the -80/-100 region (mean position -89) and is not found nearer to the Start site than -50. In TATA-less promoters it is usually closer to the +1 signal (at -66 on average) and is sometimes present in proximity to the Cap site. The consensus and location of NF-Y binding sites parallel almost perfectly a previous general statistical study on CCAAT boxes in 502 unrelated promoters. This is an indication that NF-Y is the major, if not the sole, CCAAT box recognizing protein and that it might serve different roles in TATA-containing and TATA-less promoters.